Global Health Involvement in Thyroid Cancer Incidence Increase - Lucio, Mango (International Journal of Global Health, 2020)
In recent decades was observed a gradual increase in the detection of thyroid nodules in the adult population. Given the increase in prevalence of nodules, a similar trend to the growth in the incidence of thyroid cancers was found. The reasons for this increased incidence for thyroid cancer are controversial. Increased incidence is caused by an improvement in diagnostic techniques or does not result from an overdiagnosis, but represents a real increase in the incidence of thyroid cancer? Whatever the reality, the fact of an increased incidence of thyroid cancer for certain involves problems to global health which in any case must be evaluated and corrected.
Keywords: Thyroid cancer; incidence increase; overdiagnosis; causes of increase